2021
DOI: 10.1101/2021.04.23.441083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sero-Prevalence and Risk Factor ofPeste Des Petits Ruminantsin Sheep and Goats of Ethiopia: Systematic Review and Meta-Analysis

Abstract: BackgroundPeste des petits ruminant (PPR) is the most common prevalent viral disease of sheep and goats that impacts productivity and international animal trade in the world and also in Ethiopia. Despite the huge economic consequences related to PPR, little is known about the sero-prevalence of this disease at the country levels. The objective of this systematic review and meta-analysis was to estimate a single-group summary for sero-prevalence of PPR disease in small ruminants of Ethiopia and assess the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This report is similar with other several studies (Abubakar et al, 2009;El-Yuguda et al, 2009;Enan et al, 2013;Gelana et al, 2020) and disagreed with reports that indicated PPR is more prevalent in goat than sheep (Fentie et al, 2018;Faris et al, 2012). Although sheep and goats have biological differences, increased sero-prevalence in one species than other may be caused by sampling procedures, animal abundance or distribution in a given area, management techniques, and viral strains, among other things (Yizengaw et al, 2021). PPRV may also preferentially infect goats over sheep, or vice versa, depending on the environment, and illness severity may differ between species (Truong et al, 2014).…”
Section: Prevalence Of Ppr Stratified By Different Diagnostic Test Me...supporting
confidence: 88%
See 4 more Smart Citations
“…This report is similar with other several studies (Abubakar et al, 2009;El-Yuguda et al, 2009;Enan et al, 2013;Gelana et al, 2020) and disagreed with reports that indicated PPR is more prevalent in goat than sheep (Fentie et al, 2018;Faris et al, 2012). Although sheep and goats have biological differences, increased sero-prevalence in one species than other may be caused by sampling procedures, animal abundance or distribution in a given area, management techniques, and viral strains, among other things (Yizengaw et al, 2021). PPRV may also preferentially infect goats over sheep, or vice versa, depending on the environment, and illness severity may differ between species (Truong et al, 2014).…”
Section: Prevalence Of Ppr Stratified By Different Diagnostic Test Me...supporting
confidence: 88%
“…We found a 24.74% prevalence rate among young animals and 41.23% amongst old animals. In contrast, Yizengaw et al (2021) mentioned that PPR was significantly higher in young animals (36.53%) than in adults (23.12%) and old (8.08%). According to Bari et al (2018) and Kihu et al (2015), the higher prevalence of the disease in young animals compared to older animals may be attributable to malnutrition, a less developed immune system, and inadequate husbandry techniques.…”
Section: Prevalence Of Ppr Stratified By Different Diagnostic Test Me...mentioning
confidence: 85%
See 3 more Smart Citations